Growth of Molybdenum Trioxide Nanoribbons on Oriented Ag and Au Nanostructures: A Scanning Electron Microscopy (SEM) Study. (December 2019) - Maiti, Paramita; Mitra, Arijit; Juluri, R. R.; Rath, Ashutosh; Satyam, Parlapalli V
Abstract: We report the growth of molybdenum trioxide (MoO3 ) nanoribbons (NRs) on epitaxial Ag and oriented Au nanostructures (NSs) using an ultra-high vacuum (UHV)-molecular beam epitaxy (MBE) technique at different substrate temperatures. An approximately 2 nm silver (Ag) film has been deposited at different growth temperatures (using UHV-MBE) on cleaned Si(100), Si(110), and Si(111) substrates. For faceted Au NSs, an approximately 50 nm Au film has been deposited (using high-vacuum thermal evaporation) on a Si(100) substrate with a native oxide layer at the interface and the sample was annealed in low vacuum (≈10 −2 ) and at high temperature (≈975°C). Scanning electron microscopy measurements were performed to determine the morphology of MoO3 /Ag and MoO3 /Au composite films. From energy dispersive X-ray spectroscopy elemental mapping and line scans it is found that faceted Au NSs are more favorable for the growth of MoO3 NRs than epitaxial Ag microstructures.